Principles of organization of the computer control over separate stages of the aircraft flight, using information of the onboard registers - Малежик, О.І.; Харитон, В.В.; Стефанський, С.Р. (Proceedings of National Aviation University (archive), 2004)
Recearch of the calculating processe organization’s problem concerning flight data processing operational checking crew actions and board equipment functions.